YIELD PERFORMANCE OF MUSK MELON (CUCUMIS MELO L.) AS INFLUENCED BY INTRA-ROW SPACING AND POULTRY MANURE RATE IN SAVANNA ZONE OF NIGERIA - Abubakar Ladan, Ibrahim; Adesoji, Aderemi G.; Jari, Sanusi (FUDMA Journal of Sciences, 2026)
Bilocation trials were conducted during the 2023 rainy season in Dutsin-Ma, Sudan Savanna ecological zone and Malumfashi, Northern Guinea Savanna ecological zone, Nigeria, to determine the yield response of Musk melon (Cucumis melo L.) varieties to intra-row spacing and poultry manure. The treatments comprised 2x3x4 factorial combinations of two musk melon varieties (NEPTUNE F1 and URANUS F1), three intra-row spacing treatments (25cm, 50cm, and 75cm), and four poultry manure rates (0, 5, 10, and 15 tons/ha). A Randomized Complete Block Design (RCBD) with three replications was used. URANUS F1 significantly (P
Keywords: Musk Melon; Intra-Row Spacing; Poultry Manure; Variety; Savanna